Criminal Sentence For Child Perpetrators In the Criminal Act of Sexual Interculation - Nurjanah, Ovinia; Tanuwijaya, Fanny; Prihatmini, Sapti (PT Matra Cendikia Abadi, 2024)
Children are the next generation of the nation who must be given attention, supervision, rights and protection from all forms of violence. However, child protection has a very important existence, especially in cases of child crime. Children are indeed vulnerable to crime, therefore children need extra supervision from parents and from the government through a law that regulates the protection of children from a crime. One of the criminal acts committed by children is sexual intercourse. Like the case decided by the Kolaka District Court No. 4 / Pid.Sus-Anak / 2020 / PN.Kka concerning the crime of sexual intercourse committed by children. The public prosecutor charged the child with violating Article 81 paragraph (1) and (2) in conjunction with Article 76D of Law No. 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection into Law in conjunction with Article 55 paragraph (1) ke-1 of the Criminal Code. Furthermore, the identity of children in conflict with the law must be kept confidential. In the decision of the Kolaka District Court No. 4/Pid.Sus-Anak/2020/PN.Kka which does not obscure the identity of the child. In fact, Article 10 of the Supreme Court Decree No. 144 of 2007 concerning Disclosure of Information in Court regulates the obligation to obscure the identity of children in conflict with the law (ABH). Therefore, this needs to be discussed further. In this study, the author uses a normative legal research type (Legal Research) with a statutory and conceptual regulatory approach. The conclusion of this discussion is that the child perpetrator has fulfilled the elements of